Impact of axial gravity on the transport performance of an Ω-shaped axial groove heat pipe (Ω-AGHP): A numerical investigation - Shifeng Lin; Xu Zhang; Huiying Wu (Case Studies in Thermal Engineering)
Evaporation, condensation and fluid flow within an Ω-shaped axial groove heat pipe (Ω-AGHP) are numerically simulated using the Volume of Fluid (VOF) method. The flow and thermal characteristics of the Ω-AGHP (with aluminum pipe shell and ammonia as working fluid) under various axial gravity coefficients (0, 0.1, 1.63, 3.72, 9.8, and 19.6 m/s2) are compared. It is revealed that the presence of axial gravity acting from the condenser region to the evaporator region substantially alters the vapor-liquid interface, accelerates the reflux of condensed ammonia, and therefore improves the thermal performance of the Ω-AGHP by approximately 40 %. Even a relatively low axial gravity coefficient (0.1 m/s2) can substantially boost the thermal performance of the Ω-AGHP. However, raising the gravity coefficient beyond a threshold (1.63 m/s2) does not yield additional performance improvements of the heat pipe. The results can help better understand the flow dynamics and transport mechanisms within an Ω-AGHP, offering certain engineering guidance for the design of Ω-AGHPs applied in aerospace and deep space exploration.